LOGISTICS SUPPORT AS EFFICIENT BUSINESS AND TRANSPORT - Stošić Mihajlović, Ljiljana (Journal of process management and new technologies, 2016)
Overcoming physical barriers between buyers and sellers, when the delivery of the goods in question or of passengers when it comes to passenger traffic, is the main task of logistics, practices and skills. When it concerned modern trends clearly we can say that the future has already begun. In this paper, we will point to a growing, you might say revolutionary developments in the field of passenger traffic - crossing the 1000 km in 10 minutes is no longer a figment of the imagination of talented and imaginative writers of science fiction. This is already a reality that should be expected as a mass phenomenon in the coming short-term period. When Serbia is concerned, progress is evident in logistics - as confirmed by and large, do not now recorded infrastructure projects to be implemented no later than the end of 2020.